واقع وآفاق محاسبة الموارد البشرية - علاق ،فاطمة; سالمي، محمد دينوري (جامعة الوادي University of Eloued, 2024)
الموارد البشرية هي أصول هامة للمؤسسة، ومع ذلك لا يوجد نظام قانوني للمحاسبة موارد البشرية في أي من التقارير السنوية للمؤسسة، والهدف الرئيسي من هذا الاستعراض هو دراسة فوائد ممارسات الموارد البشرية للشركة وآفاق تطبيقها، بتسليط الضوء على محاسبة الموارد البشرية من حيث المفهوم والأهداف والأهمية الخاصة بمحاسبة الموارد البشرية، والتعبير عن أساليب القياس المختلفة من محاسبة الموارد البشرية، وتسعي الورقة أيضا إلى مناقشة التسجيل المحاسبي للوصول لبيانات مالية موثوقة، والحاجة إلى محاسبة الموارد البشرية في المؤسسات في دراسة تكشف أيضا تحديات تواجهها المؤسسة خلال تنفيذ محاسبة الموارد البشرية والشرط الذي يجب أن يكون موجودا قبل اعتماد المحاسبة الخاصة بالموارد البشرية في المؤسسة. وأوصى الباحثان بضرورة تطوير نظام للمحاسبة المتعلقة بالموارد البشرية يكون مقبولا للمحاسبين والمهنيين والمديرين وغيرهم، وينبغي إخراج الموارد البشرية من الأرباح والخسائر وإظهارها في قائمة المركز المالي بتقييم الموارد البشرية كأصول. Human resources are important assets of the foundation, however there is no legal system of human resources accounting in any of the annual reports of the foundation, the main objective of this review is to study the benefits of the company's human resource practices and the prospects of their application, by highlighting human resources accounting in terms of The concept, objectives and importance of human resources accounting, and the expression of different measurement methods of human resources accounting, the paper also seeks to discuss accounting for access to reliable financial data, and the need for human resources accounting in institutions in a study also reveals Challenges faced by the foundation during the implementation of human resources accounting and the requirement that must exist prior to the adoption of human resources accounting in the organization. the researchers recommended the need to develop a system of human resources accounting acceptable to accountants, professionals, managers and others, human resources should be removed from the profits and losses and shown on the financial position list by assessing human resources as assets.
The reality and prospects of human resources accounting
Keywords: محاسبة الموارد البشرية; قياس الأداء; التسجيل المحاسبي; human resources accounting; performance measurement; accounting registration